Determination of Patient Dose on Head Computed Tomography Scan on Risk Factors of Cataract Using Size-Specific Dose Estimate (SSDE) - Palupi, Shinta; Trisnawati, Ni Luh Putu; Baskoro, Winardi Tjahyo; Irhas, Rozi (BULETIN FISIKA, 2024)
Research has been done on determining the patient's dose on a Computed Tomography (CT) Scan of the head using the Size Specific Dose Estimate (SSDE) method and the risk factors for cataracts. SSDE values ??were obtained from Computed Tomography Dose Index Volume (CTDI vol ), Anterior Posterior (AP) and Lateral (LAT) values. Data were obtained from 30 patients in the group of children aged 5-14 years and 30 patients in the adult group aged 15-50 years. The mean SSDE value for the children group was 52.387 mGy and the average value for the adult group was 49.664 mGy. The mean SSDE value of children is greater than that of adult patients, this is because the diameter of the head of the children group is smaller than the diameter of the head of the adult group. One organ that is sensitive to X-ray radiation is the eye lens. If the lens of the eye gets more than 500 Gy of radiation, it will increase the risk of cataracts. The risk factor for cataract was obtained from the SSDE value and the eye lens tissue weight factor was 0.12. The risk of cataract in this study is still below the standard value set by the ICRP in 2011 which is 500 mGy. While the percentage risk of cataract occurrence for the children group was 1.257% and for the adult group was 1.192%.